1992
DOI: 10.1021/ma00041a025
|View full text |Cite
|
Sign up to set email alerts
|

Deformation resistance in oriented nylon 6

Abstract: Initially spherulitic nylon 6 was textured into a quasi-single crystal form by plane-strain compression at 170 "C in a deep channel-die to a compression ratio of 4.0, followed by cooling under pressure to room temperature. The resulting material, having orthotropic symmetry with quasi-single crystalline perfection, had a dual morphology in which the normals of the crystallographic (100) planes equipartition at f21° with respect to the constraint direction of the plane-strain deformation. This highly textured m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(71 citation statements)
references
References 15 publications
2
69
0
Order By: Relevance
“…Clearly, this also manifests the feasibility of the strategy we proposed in the Introduction part to prepare silica/MC nylon6 in-situ nanocomposites with uniformly distributed nanoparticles. Nylon6 is well known to crystallize into variously phase: the α stable crystal and among others the γ one [18]. WAXD was used to gain insight into the influence of nano-silica on the crystal form of MC nylon6.…”
Section: Microstructural Characterizationmentioning
confidence: 99%
“…Clearly, this also manifests the feasibility of the strategy we proposed in the Introduction part to prepare silica/MC nylon6 in-situ nanocomposites with uniformly distributed nanoparticles. Nylon6 is well known to crystallize into variously phase: the α stable crystal and among others the γ one [18]. WAXD was used to gain insight into the influence of nano-silica on the crystal form of MC nylon6.…”
Section: Microstructural Characterizationmentioning
confidence: 99%
“…Argon and coworkers have also studied isotropic and single-crystal-textured samples of various semi-crystalline polymers such as polyamide 6 [31,32] and poly(ethyleneterephthalate) [33]. As in the case of PE, these authors have reported detailed analyzes of the plastic processes in terms of crystallographic slip, together with useful data of critical shear stresses and pressure sensitivity factors [31].…”
Section: Crystal Slip and Texturingmentioning
confidence: 99%
“…As in the case of PE, these authors have reported detailed analyzes of the plastic processes in terms of crystallographic slip, together with useful data of critical shear stresses and pressure sensitivity factors [31].…”
Section: Crystal Slip and Texturingmentioning
confidence: 99%
“…A channel die, the description of which is given in detail elsewhere [17,18,19,20], was used to subject the polymers to plane strain compression up to compression ratios of 12. Figure 1 shows a sketch of the channel die and defines the three principal directions, i.e., the lateral constraint direction (CD), the free (or flow) direction (FD), and the loading direction (LD).…”
Section: Experimental 1pmentioning
confidence: 99%